KETERLAKSANAAN PEMBELAJARAN GEOGRAFI PADA MASA PANDEMI COVID-19 DI SMA NEGERI KABUPATEN TANAH DATAR - Rahmat Fajar Agusti; Nofrion Nofrion (JURUSAN GEOGRAFI FIS UNP, 2021)
This study aims to determine the feasibility of learning geography during the Covid-19 pandemic, knowing the constraints of implementing geography learning during the Covid-19 pandemic, knowing the efforts of teachers in implementing geography learning during the Covid-19 pandemic at SMA Negeri Kaba District Tanah Datar. This research is a qualitative descriptive study with a case study approach method. Data collection techniques using the interview method (depth interview). The data collection tool used was the interview guide. The informants in this study were geography teachers at State Senior High Schools in Tanah Datar Regency. Data analysis techniques The analysis technique used is data reduction, data presentation and drawing conclusions The results of this study reveal that, (1) the implementation of geography learning in Tanah Datar State Senior High School is not carried out in online and combined learning (online and offline) using the Video Conference platform (Zoom Meeting, Google Meet, etc.), WhatsApp ( Chat and Group), and Google Classroom, (2) some of the obstacles experienced by students in learning such as there are still students who do not have cellphones, disruption of the internet network, there are still students who have difficulty understanding lessons online compared to face-to-face and low disciplinary awareness of student interest in learning, (3) the teacher's efforts in overcoming these problems, namely providing computer laboratory facilities and Wifi networks, giving students the opportunity to ask questions and come to school to discuss and consult with teachers, and visit students directly or call students to school.